NmsBuilder: Freeware to create subject-specific musculoskeletal models for OpenSim. (December 2017) - Valente, Giordano; Crimi, Gianluigi; Vanella, Nicola; Schileo, Enrico; Taddei, Fulvia
Highlights: nmsBuilder 2.0: freely available software to create subject-specific musculoskeletal models for OpenSim from 3D geometries. Data processing to create supporting objects, and creation of OpenSim objects. Case study: creation of a MRI-based musculoskeletal model of the lower limb for simulations of movement. nmsBuilder can help promote personalized applications in musculoskeletal biomechanics, including larger sample size studies. nmsBuilder might represent a basis for future developments for specific application in musculoskeletal biomechanics. Abstract: Background and objective: Musculoskeletal modeling and simulations of movement have been increasingly used in orthopedic and neurological scenarios, with increased attention to subject-specific applications. In general, musculoskeletal modeling applications have been facilitated by the development of dedicated software tools; however, subject-specific studies have been limited also by time-consuming modeling workflows and high skilled expertise required. In addition, no reference tools exist to standardize the process of musculoskeletal model creation and make it more efficient. Here we present a freely available software application, nmsBuilder 2.0, to create musculoskeletal models in the file format of OpenSim, a widely-used open-source platform for musculoskeletal modeling and simulation.nmsBuilder 2.0 is the result of a major refactoring of a previous implementation that moved a first step toward an efficient workflow for subject-specific model creation. Methods: nmsBuilder includes a graphical user interface that provides access to all functionalities, based on a framework for computer-aided medicine written in C++. The operations implemented can be used in a workflow to create OpenSim musculoskeletal models from 3D surfaces. A first step includes data processing to create supporting objects necessary to create models, e.g. surfaces, anatomical landmarks, reference systems; and a second step includes the creation of OpenSim objects, e.g. bodies, joints, muscles, and the corresponding model. Results: We present a case study usingnmsBuilder 2.0: the creation of an MRI-based musculoskeletal model of the lower limb. The model included four rigid bodies, five degrees of freedom and 43 musculotendon actuators, and was created from 3D surfaces of the segmented images of a healthy subject through the modeling workflow implemented in the software application. Conclusions: We have presentednmsBuilder 2.0 for the creation of musculoskeletal OpenSim models from image-based data, and made it freely available via nmsbuilder.org. This application provides an efficient workflow for model creation and helps standardize the process. We hope this would help promote personalized applications in musculoskeletal biomechanics, including larger sample size studies, and might also represent a basis for future developments for specific applications.